GC–MS Analysis of A Helichrysum italicum Hydrosol: Sensitivity, Repeatability and Reliability of Solvent Extraction versus Direct Hydrosol Analysis - Meta Kokalj Ladan; Nina Kočevar Glavač (Applied Sciences, 2022)
Hydrosols have been increasingly used in the food industries as drinks and as ingredients for seasoning and flavoring. Research has shown they have antimicrobial, antioxidative and anti-inflammatory effects and therefore have potential as food preservative agents and sanitizing agents for tools used in the food industry. The composition analysis of hydrosols is commonly conducted using extraction with organic solvents. However, some hydrophilic compounds are lost with this procedure, leading to issues in identifying native composition and potential adulteration. In this paper, different methods for hydrosol analysis are studied. The methods differ in sample preparation, number of detected compounds, repeatability and reliability. Direct hydrosol analysis and 1:1 extraction with organic solvent were determined to be the most appropriate in our experiments. However, the method implementation depends on the application. Direct hydrosol analysis is simple and does not change ratios among compounds; its drawback is poor repeatability. Using 1:1 extraction has good repeatability; however, some hydrophilic compounds are lost, and adulterations with cosolvents and the addition of solubilizers cannot be discovered.